(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Red Vine Fruits (RVFs), a wild edible fruits, are sought as an alternative food source to prevent hunger and malnutrition. This study aimed to investigate the impact of the non-nutritive compounds on the bioaccessibility of critical minerals in pre-treated RVFs using standard analytical methods. The result of mineral composition of RVFs showed that magnesium had the highest (940.33 ± 0.01), followed by potassium (389 ± 0.01), calcium (215.80 ± 0.01), and copper (2.53 ± 0.01) as the least content in mg/100 g. The non-nutritive compounds found (mg/100 g) were phytates (8430.66), oxalates (140.52), and tannins (18.19). The ratios of critical elements (Ca:K, Na:K, and Fe:Zn) were 0.54, 0.56, and 1.47, all within the standard limits except Ca:Fe, which exceeded its limit. Additionally, the molar ratios of non-nutritive compounds to critical minerals were 2.36, 102.1, 150.2, 810.5, and 0.29 for phytate: Ca; phytate: Fe; phytate: Zn; phytate*Ca: Zn; and oxalate: Ca, respectively. These values exceeded the recommended limits, but oxalate: Ca is within the safe limit. The results also depicted a moderate value in phytate K (4.04), non-phytate K (10.29), and K proportion as phytate (28.19). These values are within the maximum standard (50%) critical for optimal K bioavailability. The findings showed that RVFs are high for critical minerals with a substantial amount of non-nutritive compounds, especially phytate content, which needs to be eliminated for optimum mineral bioaccessibility.